Implementation of Electronic Budgeting in the Provincial Government of the Special Capital Region of Jakarta - Indrawan Jaya Purnama; Vishnu Juwono (Jurnal Administrasi Publik (Public Administration Journal), 2021)
This research is a case study which aims to determine the data input process along with problems in the implementation of e-budgeting in the DKI Jakarta Government and how the suitability of these processes and flows was seen from the Brinkerhoï¬€ and Crosby Policy Implementation Theory. Data collection was carried out through field observations, interviewing informants, and documentation. The collected data was then presented and analyzed qualitatively with an interactive analysis model. From the results of data analysis, it was found that the flow of budget input through the e-budgeting application system includes several stages involving government from the lowest level RT / RW to the regent / mayor, provincial DPRD, and the Ministry of Home Affairs starting from the aspiration collection stage, discussion, evaluation, and arrived at the stipulation. Problems faced in the implementation of e-budgeting include errors during budget planning and planning for regional property needs, short data input times, prices and components of goods in the e-budgeting system were not up to date, there was no component or other item that were not suitable with SKPD planning, and the existence of political intervention to support certain political activities. When viewed from Brinkerhoff and Crosby's theory of policy implementation, it was found that the e-budgeting implementation carried out in DKI Jakarta still did not fully fulfill the criteria of the policy theory. It Â can be seen from the various problems that occurred in the implementation of e-budgeting which contradicts this theory.